Research on Optimization of 3D Tourism Virtual Crossover Scene based on Semantic Perception Analysis - Guixia Wang (Advances in Multimedia)
The objective of this paper is to optimize the scene of tourism virtual perception space. Based on the abstract method of semantic feature points, the computing model of semantic perception of single-cultural landscape and multi-cultural landscape is established. Using the digital elevation model, an empirical study on the semantic perception of cultural landscape in the western Tombs of Qing Dynasty is carried out. Taking the traditional Chinese culture of the site selection of royal tombs and the feudal hierarchy represented as the semantic criteria, eighteen feature points were extracted from two representative tomb cultural landscapes from different landscape perspectives, and the corresponding weight coefficients were assigned to each feature point from different landscape perspectives; based on the results of perceptual degree calculation, the semantic mining of the existing sightseeing routes is carried out and the optimization scheme is designed. From the perspective of tourists’ perception of landscape, tourism resources are deeply mined to better reflect the value of landscape and realize the coupling and interaction between virtual tourism and tourism economy.